2008
DOI: 10.1007/s10971-008-1762-8
|View full text |Cite
|
Sign up to set email alerts
|

Core-shell effects of functionalized oxide nanoparticles inside long-range meso-ordered spray-dried silica spheres

Abstract: Core-shell and homogeneous distributions of functionalized cerium oxide nanoparticles within spraydried mesostructured silica spheres are achieved by modification of synthesis parameters such as the templating agent and nanoparticle capping functions.Keywords Mesoporous silica Á Embedded nanoparticles Á Functionalized nanoparticles Á Evaporation induced self assembly Á Spray-dryingIn the past 15 years a large number of studies has been focused on long-range ordered mesoporous materials obtained in solution thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The consistent development of technology has led to increased awareness of the importance of chemical synthesis methods, particularly those involving the use of organic precursors. One of the basic types of synthesis in which metallo-organic precursors are used to synthesize binary hybrid systems is the sol-gel method [115,116,117,118,119,120]. In recent years many definitions of the sol-gel process have been put forward, including that of Dislich and Hinz [121], which covers only multicomponent oxides.…”
Section: Methods Of Synthesis Of Titania-based Materialsmentioning
confidence: 99%
“…The consistent development of technology has led to increased awareness of the importance of chemical synthesis methods, particularly those involving the use of organic precursors. One of the basic types of synthesis in which metallo-organic precursors are used to synthesize binary hybrid systems is the sol-gel method [115,116,117,118,119,120]. In recent years many definitions of the sol-gel process have been put forward, including that of Dislich and Hinz [121], which covers only multicomponent oxides.…”
Section: Methods Of Synthesis Of Titania-based Materialsmentioning
confidence: 99%
“…It revealed that reasonably attractive interactions between NPs' surface and either silica or surfactant was needed to avoid a NPs phase separation. [ 62 ] Although homogeneously dispersed into the solution, the positive charge CTA + surfactant was found to reject aminofunctionalized NPs at the surface of the fi nal particles. In a different way, phenyl-functionalized NPs, dispersed via the addition of a fraction of THF into CTAB/silica precursor solution, were found to aggregate within the fi nal particles.…”
Section: "Ne-pot"incorporation Of Nps Into Silica Matrixmentioning
confidence: 98%
“…If one excludes reports on the incorporation of latex beads, one sees that, in a general trend, spray drying is a fl exible process allowing the introduction of large amounts (sometimes more than 10 wt%) of very different NPs such as gold, [ 41 ] TiO 2 , [ 134 ] CeO 2 , [ 62 ] or magnetic γ -Fe 2 O 3 [ 49 , 135 ] or γ -Fe 3 O 4 [ 63 ] ( Figure 8 ). The homogeneous dispersion of NPs into the mesostructured silica matrix depends mainly on two parameters, the homogeneity of the NPs dispersion into the precursor silica/surfactant solution, and the NPs'_surface/silica/surfactant interactions.…”
Section: "Ne-pot"incorporation Of Nps Into Silica Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…This upscalable and continuous method allows manufacturing mesostructured materials using soft matter chemistry in one-pot synthesis [12]. For instance, using the spray-drying technique, ceria NPs were successfully embedded in mesostructured silica spheres, showing the role of surface functional groups on the NP distribution [13]. In another work, Pd NPs were encapsulated in several types of silica mesostructures (lamellar, cubic or hexagonal) through the use of different surfactants, and exhibited high catalytic activity and ethylene selectivity in the hydrodechlorination of 1,2-dichloroethane [14].…”
Section: Introductionmentioning
confidence: 99%